Dietary Cordyceps militaris protects against Vibrio splendidus infection in sea cucumber Apostichopus japonicus. Issue 2 (August 2015) - Sun, Yongxin; Du, Xingfan; Li, Shuying; Wen, Zhixin; Li, Yajie; Li, Xuejun; Meng, Nan; Mi, Rui; Ma, Shuhui; Sun, Aijie
Abstract: Vibrio splendidus is the common pathogen that causes infectious diseases widely spread in cultured sea cucumber in China. Therefore, we investigated the ability of Cordyceps militaris to protect against infection caused by V. splendidus . In this study, sea cucumbers were fed with a diet containing 0 (control), 1%, 2% or 3% C. militaris for 28 days, and subsequently challenged with V. splendidus by injection with 1.0 × 10 9 cfu per animal. Parameters of immune response such as phagocytosis (PC), lysozyme (LSZ) activity, superoxide dismutase (SOD) activity, alkaline phosphatase (AKP) activity and acid phosphatase (ACP) activity were determined on days 0, 1, 3, 5 and 7 after injection. The results showed that dietary C. militaris at a dose of 2% or 3% significantly up-regulated ( P < 0.05) all the immune parameters on day 0. One day after injection with V. splendidus, all the immune indices except ACP exhibited a tendency to decrease and then increase again, returning to the initial level on days 5 and/or 7 after injection. All the immune parameters of those fed with C. militaris were found significantly higher ( P < 0.05) than those of the control group on day 1 after injection. Only LSZ activity of those fed with 1%- or 3%- C. militaris diet on day 5 showed significantly increases ( P < 0.05) than the controls. As for ACP activity, the values remained steady with time, but with significant increase ( P < 0.05) seen in sea cucumbers fed with 2%- C. militaris diet, and lasted for up to 7 days after V. splendidus injection. The cumulative mortality of sea cucumbers fed with the basal diet followed V. splendidus infection was significantly higher ( P < 0.05) than those fed with 2% and 3% C. militaris diet. Under the experimental conditions, dietary C. militaris could enhance the immune responses of Apostichopus japonicus and improve its resistance to infection by V. splendidus . Highlights: Daily intake of Cordyceps militaris at a dose of 2% was sufficient to elevate the immune ability of sea cucumber. One day after bacteria challenge, all the immune indices except ACP exhibited a tendency to decrease and then increase. Serum ACP activity of sea cucumber was not consistent with the other immune indices after challenge.